The isolation and translation of the messenger ribonucleic acids of the troponin complex - Durrheim, Glenda A (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.SC.(Medical Biochemistry)) -University of Stellenbosch, 1980.